Anterior scleral thickness and shape changes with different levels of simulated convergence. (February 2021) - Niyazmand, Hamed; Read, Scott A.; Atchison, David A.; Alonso-Caneiro, David; Collins, Michael J.
Abstract: Purpose: Convergence plays a fundamental role in the performance of near visual tasks. We measured the effect of two levels of convergence on anterior scleral thickness and shape in emmetropes, low to moderate myopes and high myopes. Methods: Forty-five healthy young adults aged between 18 and 35 years including 15 emmetropes, 15 low/moderate myopes, and 15 high myopes were recruited. Anterior segment optical coherence tomography and eye surface profilometry were used to evaluate the anterior scleral thickness (nasal only, n = 42) and shape (n = 40), before and during two visual tasks involving 9° and 18° convergence, in those participants with complete and reliable data. Results: Convergence led to a thickening of the total anterior eye wall (5.9 ± 1.4 μm) and forward movement (10 ± 2 μm) of the nasal anterior scleral surface (both p < 0.001). Larger changes were found at 18° than at 9° convergence and in more peripheral nasal scleral regions. There was a significant association between total wall thickening and forward movement of the scleral surface. Refractive group was not a significant main effect, but there were significant interactions between refractive group and the thickness changes with convergence in different scleral regions. Conclusion: During convergence, the biomechanical forces acting on the eye lead to nasal anterior scleral thickening and forward movement of the nasal scleral surface. Highlights: Convergence produces thickening of the nasal anterior sclera. Convergence causes forward movement of the nasal anterior sclera. Changes in thickness were significantly associated with changes in sagittal height. Greater changes occur at higher convergence and in more peripheral scleral regions. High myopes show a tendency of greater thickening with convergence.